Upaya Pengurangan Human Error Pada Kecelakaan Kerja Dengan Metode Sherpa Dan Jsa Di Perum Perhutani KBM - Industri Kayu Gresik - Rahayu, Abdi; Kholik, Heri Mujayin; Restuputri, Dian Palupi (Department Industrial Engineering, University of Muhammadiyah Malang, 2015)
Perum Perhutani KBM-IK (Kesatuan Bisnis Mandiri Industri Kayu) Gresik is a unit of the organization under the Office of Perum Perhutani Unit II East Java, which is responsible for the implementation of business management in the field of Industi Wood. In the production process, Perum Perhutani has used the modern machining tools. However, due to the negligence of the operator / worker, often causing work accident. Like do not use personal protective equipment, it is often underestimated by the operator. The method used is SHERPA to identify the source of danger while JSA used to provide solutions to the problems faced in companies. Research and calculation of risk score can be known the value of the biggest error lies in the activities taking pieces of the board after the cut using a band saw machine, cutting boards using a machine band resaw and cutting wood with a cross cut machine. The suggested solution is to further improve supervision in each process, conducting training K3 conducted by the management company, give firm sanction for operators who do not wear APD and design tools such as limiting engine band resaw and handle holder on the machine cross cut.